Determinar la época de madurez sexual de la jaiba azul callinectes sapidus en la zona sur de la provincia de El Oro - Campoverde Aleaga, Jimmy Leonardo (2006)
The present investigation one carries out in the south area of the County d and The Oro in the towns of the Pto. Hualtaco and Jelí during the months of June to November of the 2005 with the purpose of knowing the times of sexual maturity of the females of the blue Jaiba Callinectes sapidus and their partial distribution during the monitorings. They were considered the following ones characteristic. Total width of the Cefalotórax (AC). Overall length of the Cefalotórax (LC). The time of sexual maturity you determines in the female ovadas according to the coloration of their ovocitos, the same ones that differed in 4 types: orange, yellow, coffee and black. For the interpretation of the obtained data they were carried out frequency distribution analysis, lineal regression analysis and graphics of percentages. The study allowed to establish that the width and longitude of the cefalotórax don't have any relationship since with its state of sexual maturity females they were presented of small you carve ovadas. The classes of widths predominant cefalotoraxicas in the Pto. of Hualtaco and Jelí they were of the range of 9,0-9,5 cm. In the month of October you present the biggest quantity in female ovadas of orange and yellow coloration consecutively in the two ports. One of the characteristics that you could appreciate during the month of September and principles of October in Pto. Hualtaco is sexually the presence of a rosy coloration in the quelas of the mature females. The presence of female ovadas during the months of June, Julio and August was minimum, having a light growth in the month of September, in the month of October you presents the biggest quantity in female ovadas, diminishing in the month of so much November for Pto. Hualtaco like Pto stops. Jelí.